2021
DOI: 10.1088/1742-6596/1764/1/012130
|View full text |Cite
|
Sign up to set email alerts
|

Teaching STEM through play in kindergarten: analysis towards pre-service early childhood teachers preparing the lesson plan

Abstract: Integrating science with other disciplines like technology and mathematics supports early childhood have awareness and interest in science and affects their overall school performance further down in their education. The integration is commonly referred to as STEM which is an acronym of science (S), technology (T), engineering (E), and mathematics (M). STEM Education is provided to achieve educational aims that prepare people for future life and the workforce. However, designing a STEM-based learning process n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Another article reported an investigation into PSTs preparing lesson plans on STEM learning. The study revealed that PSTs consider enjoyable STEM learning experiences essential to promoting students' understanding (Rasyid et al, 2021).…”
Section: Stem Conceptualizationmentioning
confidence: 95%
See 2 more Smart Citations
“…Another article reported an investigation into PSTs preparing lesson plans on STEM learning. The study revealed that PSTs consider enjoyable STEM learning experiences essential to promoting students' understanding (Rasyid et al, 2021).…”
Section: Stem Conceptualizationmentioning
confidence: 95%
“…Our STEM-DiMRECS framework offers an EDP that defines a problem, research information, imagines the solution, plans, creates, tests and evaluates, redesigns, and communicates the solution. Electricity, home electricity instalment (Asri et al, 2021); mechanics, parabolic ball motion, collision (Yulianti et al, 2022); Newtons law, skydiving (Jannah et al, 2021); solar cell (Sukma et al, 2022); solar cell, cracker dryer (Mayasari et al, 2019); & heat, thermometer (Elfa Sari et al, 2021) Science STEMQuests: exoskeleton; wind-turbine generator; building materials; green building; piezoelectric; nanogenerator; fruits as alternative energy, recycled plastic waste (Chai et al, 2020); science projects: electric broom; simple mixer; mini vacuum cleaner; air conditioner recharger; blender; earth rotation; locomotive, mini generator (Djulia & Simatupang, 2021); balloons (Rasyid et al, 2021); rocket, catapult, paper bridge (Sumirat, 2019); human transportation system (Wahyu et al, 2020); energy (Putra et al, 2021); hyperthermia (Ismet et al, 2020) No articles in our corpus explicitly mentioned the EDP to generate the best solution in STEM learning. Most researchers describe the learning process in three phases: preparation (define the problemand explore information), generating or creating the solution, and reporting the solution, both written and oral.…”
Section: Engineering Design Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Children must have an active role in the learning process, which is called learning higher-order thinking skills, such as remembering, understanding, applying, analyzing, evaluating, and creating (Syifauzakia et al, 2021). The learning process for young children must be planned considering their cognitive abilities and learning experiences (Jatisunda et al, 2021;Rasyid et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(Syifauzakia et al, 2021). Proses pembelajaran anak usia dini harus direncanakan dengan mempertimbangkan kemampuan kognitif dan pengalaman belajar (Jatisunda et al, 2021;Rasyid et al, 2021).…”
unclassified